THE ROLE OF ISLAMIC EDUCATION TEACHERS IN SHAPING THE 'GOTONG ROYONG' CHARACTER DIMENSION AT MTSN 3 LANGKAT - Asmalia Asmalia; Arlina Arlina (SOSIOEDUKASI, 2026)
This study aims to describe the role of Islamic Education (PAI) teachers in shaping students' mutual cooperation (gotong royong) character at MTsN 3 Langkat. The character of mutual cooperation is an essential component in developing students' social attitudes, which can be manifested through learning and habituation within the school environment. This study employs a phenomenological approach, which investigates knowledge derived from consciousness or understands an object or event through conscious experience. Data were gathered through interviews with Islamic Education teachers, supplemented by field observations and documentation. Data analysis involved data reduction, data display, and conclusion drawing/verification. Data source credibility was ensured through triangulation. To guarantee data validity, the study utilized prolonged engagement, persistent observation, negative case analysis, as well as source and technique triangulation. The results indicate that Islamic Education teachers serve as role models, facilitators, and motivators in instilling the values of mutual cooperation. These values are integrated through learning materials, group discussion methods, classroom cleaning activities, and student collaboration in religious assignments. The active role of Islamic Education teachers is highly decisive in shaping students' mutual cooperation character, although synergy among the school, parents, and the social environment remains necessary for optimal character development.